(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2022)
Schizocosa malitiosa and Aglaoctenus lagotis are two wolf spiders (Lycosidae) that inhabit grasslands and hills of Uruguay. While S. malitiosa presents a wandering life habit, A. lagotis is sedentary, and lives in web. In the present study, we experimentally evaluated the capture behavior of both species on a "known" substrate and on another "unknown" one. To do this, we placed S. malitiosa (wandering) on a sand substrate and later on the A. lagotis web. At the same time we exposed to A. lagotis (sedentary), to the web substrate and later to sand. Both species captured less preys on the unknown substratum: A. lagotis: 71% on web and 35% on sand; S. malitiosa: 94% on sand, 47% on web. Likewise, A. lagotis took more time to capture the prey on sand than on web, while S. malitiosa did not differ in capture time between both substrates. The results suggest that A. lagotis has less possibilities of adapting to a substrate change, while S. malitiosa seems to adapt more easily to the change. The capture strategies used by both species on both substrates, as well as if our results support the ancestral origin of web living in Lycosidae, are discussed.